C(sp3)–F Bond Transformation of Perfluoroalkyl Compounds Mediated by Visible-Light Photocatalysis: Spin-Center Shifts and Radical/Polar Crossover Processes via Anionic Intermediates - Nishimoto, Yoshihiro; Sugihara, Naoki; Yasuda, Makoto (Synthesis, 2022)
Due to its large bond energy, precisely controllable C–F bond activation is a significant challenge in organic synthesis. A single C(sp3)–F bond transformation of perfluoroalkyl groups is particularly desirable to supply functionalized perfluoroalkyl compounds offering properties that are potentially useful in pharmaceutical and materials chemistry. Recently, the single defluorinative transformation of perfluoroalkyl compounds has been developed via visible-light photocatalysis. Herein, we summarize this field via two main topics. Topic 1 covers the transformations of C(sp3)–F bonds in either perfluoroalkylarenes or perfluoroalkane carbonyl compounds via a defluorinative spin-center shift in the radical anion intermediates. Topic 2 addresses the defluorinative transformations of α-trifluoromethyl alkenes to give gem-difluoroalkenes via a radical/polar crossover process.1 Introduction2 C(sp3)–F Transformations via Defluorinative Spin-Center Shifts3 C(sp3)–F Transformations via a Radical/Polar Crossover Process4 Conclusions
Keywords: photocatalysts; perfluoroalkyl compounds; sp3 C–F bond transformations; single-electron transfer; spin-center shift; radical/polar crossover